Consumer Perception of Sangjit Service Quality at Boosthampers Organizer Denpasar - Ni Luh Natalia Nephoye; I Nengah Wirata; Luh Putu Citrawati (Indonesian Journal of Applied and Industrial Sciences (ESA), 2025)
This study was conducted to determine how consumers perceive the quality of Sangjit service at Boosthampers Organizer Denpasar. This study uses five-dimensional analysis techniques of service quality and IPA as a reference and is a quantitative descriptive study. The results of the analysis show that consumer perceptions of service quality at Boosthampers get an average assessment based on performance of 3.67 with a good category while for assessments based on expectations, the average is 4.62. Based on the servqual gap method assessment, the level of conformity between expectations and reality is obtained at -0.95. This means that the level of consumer satisfaction is not optimal for the quality of Boosthampers Sangjit Organizer service. Based on the Cartesian diagram analysis, Boosthampers Sangjit Organizer should focus on the first quadrant (A), because in this quadrant, there are service attributes that are very important to consumers, but their performance is still low.